2020
DOI: 10.1111/os.12837
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a PEEK Material‐Based External Fixator in the Treatment of Distal Radius Fractures with Non‐Transarticular External Fixation

Abstract: Objective To explore the effect of a PEEK material‐based external fixator in the treatment of distal radius fractures with non‐transarticular external fixation. Methods There were 48 patients in this prospective comparative study. They were divided into two groups according to the materials used: the PEEK group and the titanium group. Wrist dorsiflexion, palmar flexion, pronation, supination, radial deviation, ulnar deviation, grip strength of the palm on the affected side, kneading force, Visual Analogue Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Another study reported that VLP fixation resulted in faster recovery of function compared to EF, but no functional advantage was demonstrated at two years' short follow-up [40]. Furthermore, patients undergoing DRF surgery with open reduction and internal fixation (ORIF) have a higher risk of wound infection and tendonitis [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that VLP fixation resulted in faster recovery of function compared to EF, but no functional advantage was demonstrated at two years' short follow-up [40]. Furthermore, patients undergoing DRF surgery with open reduction and internal fixation (ORIF) have a higher risk of wound infection and tendonitis [41].…”
Section: Discussionmentioning
confidence: 99%
“…First, it scarcely affects the blood supply around the fracture ends, which is conducive to recanalisation of bone vessels and creates a good fracture-healing environment. Second, non-cross-joint fixation allows normal movement of the wrist, diminishes stiffness, stimulates cartilage repair, decreases osteopenia of the distal fragment and reduces fear among patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the different surgical administration is better than other medications. 5 In addition, the pin and plaster fixation and percutaneous pinning medication are not appropriate processes for volatile distal radial fractures. Similarly, this way can bring poor results for the treatment.…”
mentioning
confidence: 99%
“…On other hand, surgical treatment is suggested for volatile and non-reducible distal radial fractures and it can be complicated. [3][4][5] Similarly, few observational studies have demonstrated the benefit of the usage of plates. In addition, most of the time external fixation is normally used in the distal radial fractures.…”
mentioning
confidence: 99%
See 1 more Smart Citation